Formulation and evaluation of simvastatin polymeric nanoparticles loaded in hydrogel for optimum wound healing purpose - Farghaly Aly U; Abou-Taleb HA; Abdellatif AH; Sameh Tolba N (Dove Medical Press, 2019)
Usama Farghaly Aly,1 Heba A Abou-Taleb,2 Ahmed AH Abdellatif,3,4 Nahla Sameh Tolba21Department of Pharmaceutics, Faculty of Pharmacy, Minia University, EL-Minia, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Nahda University (NUB), Beni-Suef, Egypt; 3Department of Pharmaceutics, College of Pharmacy, Qassim University, Al Qassim, Kingdom of Saudi Arabia; 4Department of Pharmaceutics and Industrial Pharmacy, Al-Azhar University, Assiut, Egypt Purpose: The aim of this study was to formulate a hydrogel loaded with polymeric nanoparticles (PoNPs) of simvastatin (SIM) for topical wound healing application. Materials and methods: The SIM PoNPs were prepared by using the nanoprecipitation method to improve the drug solubility and skin permeation. Furthermore, drug content, solubility, particle size, surface charge, and transmission electron microscopy of the prepared PoNPs were evaluated. Then, the PoNPs were loaded on hydrogel, and physical characteristics, in vitro release, and ex vivo permeation of the hydrogel were evaluated. Finally, the prepared gel was applied on rat wounds, and a histopathological study was performed. Results: The results showed that the drug content in the PoNPs was 86.4%. The PoNPs were spherical in shape with a smooth surface and a uniform size distribution. The particle size was 268.4±2.6, polydispersity index was ≤0.302, and zeta potential was -33±1.67 mV. The hydrogel loaded with SIM PoNPs was homogenous, and the pH was accepted and compatible with the skin. Moreover, the viscosity and spreadability assured its ease of application. The drug content was 97.25±0.02%. Furthermore, about 81% of SIM was released within 24 hours, while in the ex vivo permeation study 69.19% of SIM passed through the skin after 24 hours. Finally, the histopathological studies confirmed the efficacy of the SIM PoNPs-loaded hydrogel in wound healing due to the formation of the normal epithelial layer on day 11 after wound creation.Conclusion: The hydrogel loaded with SIM PoNPs showed a good efficacy in accelerating the healing of the rat wound with complete epithelialization and minimal inflammatory cell infiltration. Keywords: simvastatin, Carbopol® gel, ex vivo permeation, nanoprecipitaion method, wound healing